Indigenous Utilization of Resources and Conservation Practices of the Agta of Lupigue, Ilagan City, Isabela, Philippines - Geronimo, Marites C; Cabansag, Marie Grace S; Reyes, Agnes S (EDUCARE, 2016)
ABSTRACT: Indigenous environmental management for sustainability is about the particularity of place, cultural, and spiritual values woven through knowledge of wildlife, forest trees, water, and land. Indigenous values associated with natural resources utilization and conservation might defy some scientific standards as they emphasize symbolic values to indigenous identity, customary law, and environmental philosophy. Symbolic values strengthen belief to indigenous knowledge, which are priceless and are handed down from one generation to the next through apprenticeship or direct participation. Beliefs and knowledge systems require an indigenous perspective to be relevant for use, so databases from every indigenous peoples group need to be appropriately designed for specific users. This study aimed to ascertain how the Agta of Lupigue, Ilagan City, Isabela in the Philippines utilize and conserve the natural resources in their domain. The ethnographic research was used to realize the purpose of this study. In-depth interview and participant observation were rendered to gather information. A review of documentary materials and readings was done to enrich the researchersâ knowledge of the culture, knowledge systems, and practices of the respondents. Findings revealed that the Agta are consistent with their home-grown ways of using, protecting, and managing sustainably the ancestral lands and resources that have prevailed upon their identity as a people, despite the onset of science and technology. Indigenous environmental management for sustainability could be achieved by recognizing and understanding indigenous knowledge of natural resources.KEY WORDS: Indigenous Peoples; Environmental Management; Cultural and Spiritual Values; Sustainability; Indigenous Knowledge of Natural Resources.Â Â Â Â About the Authors: Marites C. Geronimo is a Lecturer at the PNU (Philippine Normal University) in Visayas, Cabahug St., Cadiz City, Negros Occidental, Philippines. Marie Grace S. Cabansag and Agnes S. Reyes are the Lecturers at the PNU (Philippine Normal University) in North Luzon, Aurora, Alicia, Isabela, Philippines. Corresponding authors is: cardona.rs@pnu.edu.phHow to cite this article? Geronimo, Marites C., Marie Grace S. Cabansag & Agnes S. Reyes. (2016). âIndigenous Utilization of Resources and Conservation Practices of the Agta of Lupigue, Ilagan City, Isabela, Philippinesâ in EDUCARE: International Journal for Educational Studies, Vol.8(2) February, pp.115-128. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (January 12, 2016); Revised (January 22, 2016); and Published (February 28, 2016).